Analisis Implementasi Tugas Pokok dan Fungsi Badan Pemberdayaan Masyarakat dan Pemerintahan Desa (BPMPD) Kabupaten Polewali Mandar - Kesuma Jaya; Andi Gau Kadir; Rabina Yunus (Departemen Ilmu Pemerintahan Fisip Unhas, 2009)
Abstract: This paper aims to describe how exercising their duties and functions of the Agency for Community Empowerment and Governance Village and factors- factors that affect the implementation process of the basic tasks and functions of the Agency for Community Empowerment and Governance Village Polewali Mandar. From the results of the study were divided into three (3) in the implementation process and the principal task of the Agency for Community Empowerment and Governance Village (BPMPD) Polewali Mandar the first phase, the technical policy formulation through strategic planning. The second phase, implementation and review programs of activities in support of the government administration. The third stage is the implementation of guidance, direction and supervision duties empowerment and village administration. The factors-factors that affect the implementation of the main tasks and functions of the Agency for Community Empowerment and Governance Village (BPMPD) the participation of village communities, LSM, community organizations then factors in rural infrastructure, human resource factor in BPMPD and village government officials and funding factors.Keywords: empowerment, the main task, implementation.Abstrak: Tulisan ini bertujuan menguraikan bagaimana pelakasanaan tugas pokok dan fungsi Badan Pemberdayaan Masyarakat Dan Pemerintahan Desa dan faktor–faktor yang mempengaruhi proses pelaksanaan tugas pokok dan fungsi Badan Pemberdayaan Masyarakat Dan Pemerintahan Desa Kabupaten Polewali Mandar. Dari hasil penelitian kemudian dibagi menjadi tiga (3) proses dalam implementasi tugas dan pokok Badan Pemberdayaan Masyarakat Dan Pemerintahan Desa (BPMPD) Kabupaten Polewali Mandar yaitu tahap pertama, perumusan kebijakan teknis melalui perencanaan strategis.Tahap kedua, pelaksanaan dan mengkaji program-program kegiatan dalam dukungan atas penyelenggaraan pemerintahan. Tahap ketiga yaitu terselenggaranya pembinaan, pengarahan dan pengawasan tugas pemberdayaan masyarakat dan pemerintahan desa. Adapun Faktor – faktor yang mempengaruhi implementasi tugas pokok dan fungsi Badan Pemberdayaan Masyarakat Dan Pemerintahan Desa (BPMPD) yaituperan serta masyarakat desa, LSM, lembaga organisasi masyarakat perdesaan kemudian faktor sarana dan prasarana, faktor SDM di BPMPD dan aparat Pemerintahan Desa dan juga faktor dana.Kata kunci: pemberdayaan, tugas pokok, implementasi